Tindakan Moral Sebagai Dasar Etika Eksistensialisme Religius Muhammad Iqbal - Hawasi, Hawasi (DAWUH : Islamic Communication Journal, 2021)
In Muhammad Iqbal’s system of thought, the discussion of ethical values does not have serious attention from scholars. It can be understood when the discussion is reduced to the fact that Iqbal was not a thinker of ethics in strict sense and he did not write the books of ethics. But, Iqbal ‘s emphasis on the virtue of man’s action and freedom, as found in his Reconstruction and poems, can categorize him as one of muslim thinkers of ethics in broad sense. This paper argues that Iqbal’s ethical view is based on his interpretation of Islam which stresses on action. In addition, Iqbal’s respect to existential freedom of man does not alienate his ethical view from God’s freedom. Therefore, in one side, Iqbal shares his idea with a religious existentialist like Kierkegaard. In the other side, he critizes ethical view as voiced by Nietzsche.